Workshop Pembuatan Chips Tulang Ikan Lele untuk Menumbuhkan Karakter Kewirausahan Anak - Achmad Zainuddin; Adinda Salsabila Kurnia; Ahmad Sirojuddin; Ahmad Walid Hujairi; Ajeng Kinanti Anastasia; Aizzatul Izzah; Alfina Dea Aninda; Almirah Inas Tsabitah; Andiya Fansa Eravani Wiyanto; Atika Aulia Puspita; Cholifah Tur Rosidah (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2024)
This workshop was motivated by the potential of Wadungasri village where there is processing of Dimsum from catfish meat. The aim of this workshop is to foster an entrepreneurial spirit in elementary school students in preparing them to learn to become creative and innovative future entrepreneurs and implement it in P5 activities at school and instill character traits in students. Apart from that, students are taught to utilize the potential around them through economic activities (production, distribution and consumption). The data collection technique used is descriptive. It is hoped that the results of this workshop can instill character values in children, which are reflected in the product packaging, namely positive character when eating.